2018
DOI: 10.1016/j.celrep.2018.08.086
|View full text |Cite|
|
Sign up to set email alerts
|

BRCA1 Mutation-Specific Responses to 53BP1 Loss-Induced Homologous Recombination and PARP Inhibitor Resistance

Abstract: SUMMARY BRCA1 functions in homologous recombination (HR) both up- and downstream of DNA end resection. However, in cells with 53BP1 gene knockout (KO), BRCA1 is dispensable for the initiation of resection, but whether BRCA1 activity is entirely redundant after end resection is unclear. Here, we found that 53bp1 KO rescued the embryonic viability of a Brea1ΔC/ΔC mouse model that harbors a stop codon in the coiled-coil domain. However, Brca1ΔC/ΔC;53bp1−/− mice were susceptible to tumor formation, lacked Rad51 fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
68
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(75 citation statements)
references
References 59 publications
(121 reference statements)
6
68
0
1
Order By: Relevance
“…Moreover, partial loss of the BRCA1-PALB2 interaction in PALB2 +/CC6 RNF168 À/À cells phenocopied the HR defects of BRCA1 +/D11 RNF168 À/À cells. These findings were largely consistent with that of Johnson and colleagues demonstrating that efficient RAD51 loading and HR requires BRCA1 hypomorphic alleles that retain the ability to associate with PALB2 (Nacson et al, 2018). In fact, a very important but still poorly understood aspect in the etiology of BRCA1-mediated breast or ovarian carcinogenesis relates to the different nature of germline BRCA1 mutations.…”
supporting
confidence: 88%
“…Moreover, partial loss of the BRCA1-PALB2 interaction in PALB2 +/CC6 RNF168 À/À cells phenocopied the HR defects of BRCA1 +/D11 RNF168 À/À cells. These findings were largely consistent with that of Johnson and colleagues demonstrating that efficient RAD51 loading and HR requires BRCA1 hypomorphic alleles that retain the ability to associate with PALB2 (Nacson et al, 2018). In fact, a very important but still poorly understood aspect in the etiology of BRCA1-mediated breast or ovarian carcinogenesis relates to the different nature of germline BRCA1 mutations.…”
supporting
confidence: 88%
“…In Brca1 5382stop/− mouse tumors, no truncated BRCA1ΔBRCT proteins can be detected either [50]. Similarly, no truncated BRCA1ΔC proteins can be found in Brca1 ΔC/ΔC cells [56]. In agreement with these observations in mouse cells, truncated BRCA1ΔBRCT proteins cannot be detected either in several human cancer cell lines with truncating mutations at BRCA1 BRCT domains [56,57].…”
Section: Mice With Brct Domain Disruptionssupporting
confidence: 73%
“…Unlike the lethality of Brca1 Δ5-6/Δ5-6 null ES cells, viable Brca1 Δ22-24/Δ22-24 ES cells can be obtained by Cre-mediated incision in Brca1 F22-24/Δ22-24 ES cells [55]. An allele that disrupt both CC and BRCT domains, Brca1 ΔC , is recently generated [56]. Mice homozygous for this allele is also lethal, but embryonic development is not analyzed.…”
Section: Mice With Brct Domain Disruptionsmentioning
confidence: 99%
“…Taken together with previous findings 18,19 , our data thus indicated that BRCA1 is critical for RAD51 filament formation and ensuing HR. In light of this, we concluded that the pronounced effects of BRCA1 loss on RAD51 filament formation and HR might largely reflect BRCA1's crucial role(s) associated with recruitment of the PALB2-BRCA2-RAD51 complex to RPA-coated ssDNA 6,7,20 .…”
Section: Resultsmentioning
confidence: 92%